2017
DOI: 10.1002/ep.12690
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of transesterification process using homogeneous and nano‐heterogeneous catalysts for biodiesel production from Mangifera indica oil

Abstract: The Mangifera indica oil is a nonedible vegetable oil, which is available in large quantities in mango cultivating countries including India. Very little published work has been found on transesterification process. In present study, the transesterification processes with homogeneous catalysts like NaOH, KOH and heterogeneous solid catalysts like nano MgO (crystal size 6-42 nm, BET surface area 50 m 2 /gm), nano ZnO (crystal size 15-48 nm, BET surface area 12 m 2 / gm), and nano SiO 2 (crystal size 1-44 nm, BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The various influence of the temperature on FAME and TA content in the interesterification referred to in this work could be similar to the influence of reaction time, and therefore it seems to be very feasible. It has been shown that the raising of temperature in transesterification reactions cannot increase the FAME content in all cases [15] and also can occur in some reactions with maxima for all variables [1]. In all cases such result could be explained by the influence of different side reactions, proceeding in the presence of catalyst as competing for the desired ones.…”
Section: Composition Of Reaction Mixtures and Reaction Kineticsmentioning
confidence: 98%
“…The various influence of the temperature on FAME and TA content in the interesterification referred to in this work could be similar to the influence of reaction time, and therefore it seems to be very feasible. It has been shown that the raising of temperature in transesterification reactions cannot increase the FAME content in all cases [15] and also can occur in some reactions with maxima for all variables [1]. In all cases such result could be explained by the influence of different side reactions, proceeding in the presence of catalyst as competing for the desired ones.…”
Section: Composition Of Reaction Mixtures and Reaction Kineticsmentioning
confidence: 98%
“…One example is heterogeneous catalyst which is environmentally friendly and recyclable. They are capable of producing high yield of biodiesel and can be separated from the liquid easily apart from possess a long lifespan [51,125]. A study by Tahvildari et al used CaO and MgO heterogenic nano-catalyst coupling for the transesterification reaction to produce biodiesel from recycled cooking oil.…”
Section: Acid/base and Enzyme Catalysismentioning
confidence: 99%
“…The results indicated that nano-SiO 2 had the highest yield due to its super-acidity characteristics that had a positive effect on the catalytic reactivity. Nano-SiO 2 also performs as a robust activators which can stimulate the reaction to obtain maximum yield [51]. The development of Ag/bauxite nanocomposites for biodiesel production has also been performed [52].…”
Section: Acid/base and Enzyme Catalysismentioning
confidence: 99%
“…In that sense, homogeneous catalysis is still economically feasible, requiring washing treatments and the subsequent water treatment to neutralize the corresponding catalyst [21]. This way, many researchers have compared homogeneous catalysts (both acid and base) with other kinds of catalysts, such as heterogeneous or nano-heterogeneous catalysts, taking the former as a reference to compare the efficiency of the process [18,[22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%